Animal Model of Chronic Migraine‐Associated Pain. Issue 1 (13th February 2018) - Moye, Laura S.; Pradhan, Amynah A. A.
Abstract: Migraine is a debilitating condition that affects hundreds of millions of people worldwide. A subset of these patients experience chronic migraine, resulting in long‐term disability and a severely lowered quality of life. The development of novel migraine therapies has been slow, partially due to the small number of predictive animal models. We have recently developed a novel model of chronic migraine‐associated pain, using the known human migraine trigger, nitroglycerin. Injection of nitroglycerin evokes an acute mechanical hyperalgesia, which is sensitive to the acute migraine therapy sumatriptan. In addition, chronic administration of nitroglycerin produces a progressive and sustained decrease in basal mechanical responses, and this hypersensitivity is blocked by migraine preventatives such as topiramate. This mouse model of chronic migraine can be used to study the mechanisms underlying progression of migraine from an episodic to a chronic disorder, and for identifying and screening novel acute and preventive migraine therapies. © 2017 by John Wiley & Sons, Inc.